Solution structures of multiple G-quadruplex complexes induced by a platinum(II)-based tripod reveal dynamic binding - Wenting Liu (Nature Portfolio, 2018)
DNA G-quadruplexes occur in oncologically relevant regions, thus are interesting targets for cancer research and treatment. Here, the authors solved the 1:1 and 4:2 (ligand/DNA) NMR structures of human telomeric DNA in complex with platinum(II)-tripod ligand and show that the binding is dynamic.